Integrated Micro-Devices for a Lab-in-Organoid Technology Platform: Current Status and Future Perspectives - Angotzi, Gian Nicola; Giantomasi, Lidia; Ribeiro, Joao F.; Crepaldi, Marco; Vincenzi, Matteo; Zito, Domenico; Berdondini, Luca (Frontiers in Neuroscience, 2022)
Advancements in stem cell technology together with an improved understanding of in vitro organogenesis have enabled new routes that exploit cell-autonomous self-organization responses of adult stem cells (ASCs) and homogenous pluripotent stem cells (PSCs) to grow complex, three-dimensional (3D), mini-organ like structures on demand, the so called organoids. Conventional optical and electrical neurophysiological techniques to acquire functional data from brain organoids, however, are not adequate to chronically record neural activity from these model systems, and are not ideal approaches for throughput screenings applied to drug discovery. To overcome these issues, emerging new approaches aim at fusing sensing and/or actuating artificial devices within organoids. Here we introduce and develop the concept of the Lab-in-Organoid (LIO) technology for in-tissue sensing and actuation within 3D cell aggregates. This technology grounds on the self-aggregation of brain cells and integrated bioelectronic micro-scale devices to provide an advanced tool for generating 3D biological brain models with in-tissue artificial functionalities adapted for routine, label-free functional measurements and for assay’s development. We report and discuss the latest advances on the implementation of the integrated self-standing wireless silicon micro-devices, including circuit solutions, simulation results and experimental measurements of the preliminary prototype realized in a 130 nm RF-CMOS technology. Finally, we discuss the technology headway and future perspectives.